The European Union and Latin America and the Caribbean vis-à-vis the 2030 Agenda for Sustainable Development : the environmental big push (ECLAC SantiagoCL, 2016)
Gives an overview of the main determinants of the economic, production, social and environmental circumstances of European Union and CELAC countries.
Keywords: SUSTAINABLE DEVELOPMENT